2011
DOI: 10.1007/s00540-011-1111-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of unilateral spinal anesthesia at different speeds of intrathecal injection

Abstract: The result of the study show that the extra-slow injection of hyperbaric bupivacaine provided strictly unilateral sensorial and sympathetic block in 93.9 and 87.9% of the patients, respectively, and that a slow injection of low doses of hyperbaric 0.5% bupivacaine 1 ml was sufficient to provide unilateral spinal anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(27 reference statements)
1
9
1
Order By: Relevance
“…In this study we achieved a success rate of 98% in achieving a unilateral spinal block, which is greater than the success rates of 13% to 94% described in other studies [6][7][8][9]12,13,[18][19][20] . The wide range of success reported probably reflects the lack of a standardised procedure for performing the spinal block.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In this study we achieved a success rate of 98% in achieving a unilateral spinal block, which is greater than the success rates of 13% to 94% described in other studies [6][7][8][9]12,13,[18][19][20] . The wide range of success reported probably reflects the lack of a standardised procedure for performing the spinal block.…”
Section: Discussioncontrasting
confidence: 54%
“…Of these, the injection rate appears to be the most important factor. Two studies directly compared the effect of different injection rates and found better success achieving a unilateral effect with a slower injection 12,13 . With an injection rate of 0.5 ml/min, which is 33% faster than that used in this study, the success rates were 48% 12 and 94% 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after use of hyperbaric anesthetics the incidence of hypotension is as much as 60–90% during the perioperative period [ 9 15 ]. This is related to both the rapid onset of analgesia in spinal anesthesia and the characteristics of hyperbaric anesthetics, such as the uncontrolled upper plane of anesthesia [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the patients were turned to lateral position on the operation side for 15 minutes and intratechal injection time was about 40 seconds. The effect of different speeds of intrathecal injection on the unilateral spinal block formation is controversial (19,20).…”
Section: Discussionmentioning
confidence: 99%